Increased Breast Density on Screening Mammography: Laws Leading to Confusion Amongst Providers [38K]. (May 2017) - Mirghani, Sara; Goldberg, Jay; Jaspan, David; Copit, Debra; Scaven, Christopher
Abstract : INTRODUCTION: The breast density notification act is a law that mandates that providers notify patients with increased breast density on screening mammography and offer these patients additional breast imaging. The American College of Obstetricians and Gynecologists has concluded that no studies have demonstrated improved prognosis when additional imaging is obtained, however they state that physicians should comply with their state laws. The aim of this project is to assess providers' knowledge of and management of increased breast density. METHODS: An anonymous nine question survey was administered to obstetrician gynecologist residents and attending physicians and primary care physicians. It was sent to providers via email through a Survey Monkey link. Data was collected over a two-month period with a total of 64 responses. RESULTS: Only 32% of providers understand the clinical significance of increased breast density on mammography. Only 21% of providers discuss the option of additional imaging with patients who have increased breast density. Sixty-one percent of providers are unaware of the Breast Density Notification Act. Approximately, 47% of providers stated that they would now change their management of increased breast density on mammogram, after having read the Breast Density Notification Act. CONCLUSION: There is a lack of provider knowledge regarding the finding of increased breast density on screening mammography. Most providers do not comply with state breast density laws. Simple interventions, such as clinician education and reformatting screening mammography result letters to both patients and providers can improve compliance with breast density notification laws and limit legal liability.